Pelatihan Mengelola Homestay di Desa Wisata Donokerto - Damasdino Damasdino (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
Managing Homestay Training in the Tourism Village of Donokerto. Donokerto Village is one of the pioneering tourist villages that has quite a good potential in terms of the diversity of tourist attractions. In addition to tourist attractions, as the main factor triggering a visit, Homestay is one of the main sources of income which is very strategic to be taken into account in every management of a tourist village. Remembering Homestay is a basic need for every tourist who wants to visit to enjoy the attraction of the village in a long time As a tourism village that is being pioneered, Donokerto Village does not yet have human resources or a community that understands the ins and outs of Homestay management. Therefore, AMPTA Yogyakarta College of Tourism in collaboration with PUM Netherlands Senior Experts held community service with the theme